A case of renal liposarcoma - Koike, H (Hinyokika kiyo. Acta urologica Japonica, 1994)
A-48-year-old male was admitted to our hospital with a right renal tumor. He received radical nephrectomy immediately. Histological examination of surgical specimen revealed renal liposarcoma, which consisted of mixed type of pleomorphic and well differentiated subtypes. Multiple tumorous lesions were scattered in the renal parenchyma. He has been alive without disease for 2 years and 7 months after surgery. Only 23 cases of renal liposarcoma have been reported in Japan